2020
DOI: 10.1002/app.49513
|View full text |Cite
|
Sign up to set email alerts
|

Improved tribological and noise suppression performance of graphene/nitrile butadiene rubber composites via the exfoliation effect of ionic liquid on graphene

Abstract: Minimization and suppression of friction and noise in underwater bearings remains a key aspect in modern marine vehicle industry owing to the growing need for reliability, and passenger comfort. In this study, graphene nano‐flake (Gr) was introduced into the nitrile butadiene rubber (NBR) with assistance of ionic liquid (IL). Owing to the positive charge generated by the secondary ordering layer on the Gr surface, Gr were effectively exfoliate into few layers and uniformly dispersed in the NBR matrix. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The nitrile butadiene rubber (NBR) with ionic liquid exfoliated graphene exhibits an increase in hardness, tear strength, and compressive modulus by 8%, 24%, and 25%, respectively due to the absence of graphene aggregates. 80 Ball milling is also practiced for producing a methyl methacrylate/NBR/GO composite. Methyl methacrylate and NBR are premixed and then ball milled with GO using 5, 8, 10, 12, and 15 mm zirconia balls (ratio of 6 : 5 : 5 : 2 : 2) respectively, and a ball powder ratio of 3.87 at 400 rpm for 300 minutes.…”
Section: Graphenementioning
confidence: 99%
See 2 more Smart Citations
“…The nitrile butadiene rubber (NBR) with ionic liquid exfoliated graphene exhibits an increase in hardness, tear strength, and compressive modulus by 8%, 24%, and 25%, respectively due to the absence of graphene aggregates. 80 Ball milling is also practiced for producing a methyl methacrylate/NBR/GO composite. Methyl methacrylate and NBR are premixed and then ball milled with GO using 5, 8, 10, 12, and 15 mm zirconia balls (ratio of 6 : 5 : 5 : 2 : 2) respectively, and a ball powder ratio of 3.87 at 400 rpm for 300 minutes.…”
Section: Graphenementioning
confidence: 99%
“…The vibration and noise suppression effect also improved by referring to the reduction of vibration acceleration level from 111.37 dB to 79.68 dB when 2 wt% of graphene is added. 80 Likewise, a damping system is created by reinforcing a few layers of graphene and carbonyl iron particles into the styrene butadiene forming a magnetorheological elastomer. With the addition of 2 vol% of few-layer graphene, the fracture toughness increases from 1.8 MJ m −3 to 4 MJ m −3 which is ascribed to the high surface area of graphene forming a hybrid filler–rubber network.…”
Section: Graphene Materials and Their Hybrids' Application In Various...mentioning
confidence: 99%
See 1 more Smart Citation
“…One common way is to incorporate self-lubricating fillers into the PU matrix. 6 Golaz investigated the effects of graphite, TiO 2 , MoS 2 , SiO 2 , and ZrO 2 particles on the tribological properties of wax-containing PU composites and revealed that the lowest friction coefficient of 0.53 was achieved at 10 wt % ZrO 2 and 15 wt % MoS 2 . 7 Yang utilized the strong load-carrying ability of multiwalled carbon nanotubes and the excellent lubricant capacity of MoS 2 to greatly reduce the friction coefficient of the PU coating.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are two main strategies to ameliorate the tribological performance of the PU material. One common way is to incorporate self-lubricating fillers into the PU matrix . Golaz investigated the effects of graphite, TiO 2 , MoS 2 , SiO 2 , and ZrO 2 particles on the tribological properties of wax-containing PU composites and revealed that the lowest friction coefficient of 0.53 was achieved at 10 wt % ZrO 2 and 15 wt % MoS 2 .…”
Section: Introductionmentioning
confidence: 99%